Use of response surface methodology for the optimization of the lipase-catalyzed synthesis of mannosyl myristate in pure ionic liquid - Galonde, Nadine; Brostaux, Yves; Richard, Gaetan; Nott, Katherine; Jérôme, Christine; Fauconnier, Marie-Laure (Process Biochemistry, 2013)
peer reviewed The purpose of the present study is to find the conditions allowing to reach the highest 24 h-yield(24 h- ) for the synthesis of mannosyl myristate catalyzed by the immobilized lipase B from Candida antarctica (Novozym®435) in the ionic liquid (IL) [Bmpyrr][TFO] (1-butyl-1-methylpyrrolidinium tri-fluoromethanesulfonate). A full factorial design (FFD) was used in order to study the influence of three variables (temperature, mannose/vinyl myristate ratio and total substrate quantity) on the 24 h- . This design led to a model based on a second order polynomial response function. The resulting predicted con-tour plots have shown that the highest 24 h- should be obtained with high temperatures, low sugar/vinylester molar ratio and intermediate total substrate quantities (mmol). The model has been successfully verified and experimentally confirmed at the optimal conditions of 80◦C, substrate molar ratio of 1/10and total substrate quantity of 0.26 mmol leading to the highest predicted 24 h- of 72.2%.